Relationship of Work Related Factors to the Adherence of Staff Nurses of Hospitals in Marawi City, Philippines to Infection Control Protocol - Manalocon- Basher, Salmah Lao (JPAIR Multidisciplinary Research, 2016)
Infection control is one of the hospital policies that prevents and controls the occurrence of hospital-acquired infections. The study aimed to determine the adherence of staff nurses of hospitals in Marawi City and its relationship to the factors affecting their adherence to the said protocol. The study was conducted in the different hospitals in Marawi City. The respondents were the 60 staff nurses working in the different institutions of the city and 50 significant others who were staying with the patient for not less than 3 days of confinement. The study utilized the quantitative research design aimed at descriptive correlation analysis on the adherence of staff nurses on infection control protocol and the factors affecting their compliance to it. The tools composed of questionnaires and checklists. Frequencies, percentages, and spearman rho correlation were the statistical tools utilized. The findings of the study showed that 73.3% staff nurses were moderately adhering to infection control protocol and this is affected by some variables under the workload, work set-up, cultural practices, administration and supervision. These are also the variables having significant relationship to the adherence of staff nurses to infection control.